2006
DOI: 10.1021/es062994k
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Air Quality—Measures with Co-Benefits in China

Abstract: Climate Changeand Air Quality-Measures with Co-Benefits in CHINA A lthough the Kyoto Protocol is an important step, its impact on global warming, seen in isolation, will be small. Broader participation and deeper cuts in greenhouse-gas (GHG) emissions are essential for any post-Kyoto agreement to have a significant effect. Particularly important are the prospects for curbing GHG emissions in large developing countries, such as China and India, whose CO 2 emissions are projected to grow dramatically over the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…These results agree well with other studies Vignati et al, 2010). Since the climate impact of BC aerosols depends on their vertical location, it is important to both measure and model the vertical distribution of BC properly (Ban-Weiss et al, 2011;Koch and Del Genio, 2010). Comparison with vertical profiles shows that the model generally overestimates the BC concentration, especially at higher altitudes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results agree well with other studies Vignati et al, 2010). Since the climate impact of BC aerosols depends on their vertical location, it is important to both measure and model the vertical distribution of BC properly (Ban-Weiss et al, 2011;Koch and Del Genio, 2010). Comparison with vertical profiles shows that the model generally overestimates the BC concentration, especially at higher altitudes.…”
Section: Discussionsupporting
confidence: 89%
“…The climate effects of BC particles depend on their altitude in the atmosphere (Ban-Weiss et al, 2011;Johnson et al, 2004;Koch and Del Genio, 2010;Samset and Myhre, 2011) and it is important to properly measure and model the vertical distribution. BC aerosols at high altitudes are more likely to be above clouds and thus have a stronger direct effect due to cloud reflection from below Satheesh, 2002).…”
Section: Global Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning climate change mitigation and adaption, the Kyoto Protocol is a very important step for reducing GHG emissions, and, moreover, broader participation and deeper cuts in GHG emissions are essential for any post-Kyoto agreement [6]. However, the common recognition on reducing GHG emissions from the past several Conferences of Parties (COP) to the United Nations Framework Convention on Climate Change, such as the COP 15 in 2009 of Copenhagen, COP 17 in 2011 of Duban and COP19 in 2013 of Warsaw are not sufficient enough.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far it has not been adequately considered in policy making in many developing countries. A number of studies reported applications of the modeling tool to investigate impacts of emission reduction measures on the premature mortality and radiative forcing in East and South Asia (Saikawa et al, 2009;Aunan et al, 2006;Akimoto et al, 2015). There are no such detailed studies conducted for the SEA region where local/domestic and transboundary problems, e.g., regional haze, are important (Heil and Goldammer, 2001).…”
Section: Introductionmentioning
confidence: 99%